Using soundscapes to detect variable degrees of human influence on tropical forests in Papua New Guinea. Issue 1 (31st October 2017) - Burivalova, Zuzana; Towsey, Michael; Boucher, Tim; Truskinger, Anthony; Apelis, Cosmas; Roe, Paul; Game, Edward T.
Abstract: There is global concern about tropical forest degradation, in part, because of the associated loss of biodiversity. Communities and indigenous people play a fundamental role in tropical forest management and are often efficient at preventing forest degradation. However, monitoring changes in biodiversity due to degradation, especially at a scale appropriate to local tropical forest management, is plagued by difficulties, including the need for expert training, inconsistencies across observers, and lack of baseline or reference data. We used a new biodiversity remote‐sensing technology, the recording of soundscapes, to test whether the acoustic saturation of a tropical forest in Papua New Guinea decreases as land‐use intensity by the communities that manage the forest increases. We sampled soundscapes continuously for 24 hours at 34 sites in different land‐use zones of 3 communities. Land‐use zones where forest cover was fully retained had significantly higher soundscape saturation during peak acoustic activity times (i.e., dawn and dusk chorus) compared with land‐use types with fragmented forest cover. We conclude that, in Papua New Guinea, the relatively simple measure of soundscape saturation may provide a cheap, objective, reproducible, and effective tool for monitoring tropical forest deviation from an intact state, particularly if it is used to detect the presence of intact dawn and dusk choruses. Abstract : Article impact statement : Recording animal sounds helps with conservation planning in tropical forests where traditional surveys are impractical.